Alsophylax przewalski (Reptilia, Gekkonidae): некоторые номенклатурные трудности - Голубев, М.Л. (Вестник зоологии, 1984)
Gymnodactylus microtis Blanford, 1875 is resurrected from sy- nonymy of Lacerta pipiens Pallas, 1811 and established to be a nomen oblitum of Alsophylax przewalski Strauch, 1887. Lectotype and paralectotypes are designated in the collection of Zoological Institute, USSR Academy of Sciences, Leningrad; a paralecto- type in collection of the U.S. National Museum of Natural History, Smithsonian Institu- tion, Washington, D.C. The type-specimen of G. microtis has not been examined, since Zoological Survey of India (Calcutta) negatively responded all inquiries to lend this material.